2022
DOI: 10.35723/ajie.v6i2.249
|View full text |Cite
|
Sign up to set email alerts
|

Quality Islamic Boarding School Model: Linking the Principles of Teacher Professionalism and Organizational Management

Abstract: Contradictory professional and managerial principles such as quality monitoring and evaluation are integrated to shape contemporary professional action. This study aims to determine the directions of teacher professionalism and organizational management as a quality control model in Islamic boarding schools/dayah in Southeast Aceh district. This type of qualitative research with descriptive survey techniques. Primary data sources were obtained from informants and survey results, while preliminary data was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Moreover, universities can maximize the function of alumni. According to Didi's research findings, one of the primary instruments of the university's benchmarking strategy is maximizing the alumni's participation in society (Andersson & Djeflat, 2013;Rahmah et al, 2022).…”
Section: Excellence In Quality Improvementmentioning
confidence: 99%
“…Moreover, universities can maximize the function of alumni. According to Didi's research findings, one of the primary instruments of the university's benchmarking strategy is maximizing the alumni's participation in society (Andersson & Djeflat, 2013;Rahmah et al, 2022).…”
Section: Excellence In Quality Improvementmentioning
confidence: 99%
“…The application of TQM is able to increase consumers and improve quality continuously. Then, research conducted by Rahmah and shows TQM has a positive and significant effect on performance (Marquez et al, 2022;Rahmah & Prasetyo, 2022;Singhania et al, 2022). The aims of this study is to analyze the effectiveness of benchmarking techniques in improving educational services in Public Vocational High School.…”
Section: Introductionmentioning
confidence: 98%
“…The hypothesis in this study is that participatory leadership significantly impacts the formation of high-quality schools. Rahmah, Berkovich, and their colleagues discovered that school quality is influenced by work motivation (Berkovich & Bogler, 2020); (Rahmah & Prasetyo, 2022); (Susetyo et al, 2022). Rahmah, Berkovich, and their colleagues disMeanwhile, Uline and Valen's research found that the size of a good school is determined by its infrastructure and facilities.…”
Section: Introductionmentioning
confidence: 99%